Influence of filler hybridization on thermomechanical properties of hemp/silver epoxy composite. Issue 9 (November 2021) - Siva Kumar, Munjula; Kumar, Santosh; Gouda, Krushna; Bhowmik, Sumit
The polymer composite material's thermomechanical properties with fiber as reinforcement material have been widely studied in the last few decades. However, these fiber-based polymer composites exhibit problems such as fiber orientation, delamination, fiber defect along the length and bonding are the matter of serious concern in order to improve the thermomechanical properties and obtain isotropic material behavior. In the present investigation filler-based composite material is developed using natural hemp and high thermal conductive silver nanoparticles (SNP) and combination of dual fillers in neat epoxy polymer to investigate the synergetic influence. Among various organic natural fillers hemp filler depicts good crystallinity characteristics, so selected as a biocompatible filler along with SNP conductive filler. For enhancing their thermal conductivity and mechanical properties, hybridization of hemp filler along with silver nanoparticles are conducted. The composites samples are prepared with three different combinations such as sole SNP, sole hemp and hybrid (SNP and hemp) are prepared to understand their solo and hybrid combination. From results it is examined that, chemical treated hemp filler has to maximized its relative properties and showed, 40% weight % of silver nanoparticles composites have highest thermal conductivity 1.00 W/mK followed with hemp filler 0.55 W/mK and hybrid 0.76 W/mK composites at 7.5% of weight fraction and 47.5% of weight fraction respectively. The highest tensile strength is obtained for SNP composite 32.03 MPa and highest young's modulus is obtained for hybrid composites. Dynamic mechanical analysis is conducted to find their respective storage modulus and glass transition temperature and that, the recorded maximum for SNP composites with 3.23 GPa and 90°C respectively. Scanning electron microscopy examinations clearly illustrated that formation of thermal conductivity chain is significant with nano and micro fillers incorporation.